Thermodynamical characteristics of monsoon troposphere over the Bay of Bengal - SINGH, O. P. (MAUSAM, 1999)
Thermodynamical characteristics of monsoon troposphere, especially the lower troposphere, over different regions of Bay of Bengal has been studied utilising the radiosonde data collected by Ocean Research Vessel (ORV) Sagar Kanya during the period 8 July-5 August, 1991. The results reveal the existence of low level inversions over the central and adjoining parts of southern Bay of Bengal between 13.4°-17.2°N and 84.5°- 90.0°E during July-August The lower troposphere upto 850 hPa appears to be absolutely stable over this region of Bay of Bengal. In total contrast, none of the ascents taken over the region north of 17.7°N showed any low level inversion. The lower troposphere over the northern Bay of Bengal where convection develops under favourable synoptic situations in monsoon, was found to be unstable. In July the low level inversion appears to extend far south (upto about 10.3°N) but gets disintegrated over the southern parts of Bay of Bengal with the advance of season. Many ascents over the northern and central Bay of Bengal have shown the occurrence of stable layers near 0° level. In the equatorial Bay of Bengal between 5°-10°N stable layers appear to exist near 400 hPa level and near 850-800 hPa level. The results seem to provide an insight into the pattern of convection over the Bay of Bengal during monsoon.